If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 4 + -3(x + -1) Reorder the terms: 7x = 4 + -3(-1 + x) 7x = 4 + (-1 * -3 + x * -3) 7x = 4 + (3 + -3x) Combine like terms: 4 + 3 = 7 7x = 7 + -3x Solving 7x = 7 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 7x + 3x = 7 + -3x + 3x Combine like terms: 7x + 3x = 10x 10x = 7 + -3x + 3x Combine like terms: -3x + 3x = 0 10x = 7 + 0 10x = 7 Divide each side by '10'. x = 0.7 Simplifying x = 0.7
| 3x+11=7x+3 | | 6(y-3)=24 | | 240=4w+11g | | x+7-3x=16-5x+3 | | 1.2x=.72 | | 5x-20+3=7x | | 4=7w+6 | | 4x+6=2(x+8) | | 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) | | 2(x-8)=2x+6 | | 2x^2+10X+3=3 | | 4.5g+0.75=18.75 | | 4.5+0.75=18.75 | | 3x=5(x+3)-s | | f(x)=3x^2-9x+6 | | -4=2-3p | | 4k-5=-17 |